2020
DOI: 10.1145/3421712
|View full text |Cite
|
Sign up to set email alerts
|

CrowdWT

Abstract: Crowdsourcing is a relatively inexpensive and efficient mechanism to collect annotations of data from the open Internet. Crowdsourcing workers are paid for the provided annotations, but the task requester usually has a limited budget. It is desirable to wisely assign the appropriate task to the right workers, so the overall annotation quality is maximized whilst the cost is reduced. In this paper, we propose a novel task assignment strategy (CrowdWT) to capture the complex interactions between tasks and worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Choose the air curtain attack method, and update the individual position according to formula ( 16 According to formula (13) and formula (14), perform local dithering on the optimal individual…”
Section: Startmentioning
confidence: 99%
See 1 more Smart Citation
“…Choose the air curtain attack method, and update the individual position according to formula ( 16 According to formula (13) and formula (14), perform local dithering on the optimal individual…”
Section: Startmentioning
confidence: 99%
“…In addition to considering the position match between the user and the task, Zhao et al 13 started from the homogeneity of humans and applied the relationship between friends in social networks to task allocation scenarios, and proposed a task allocation algorithm based on friend relationships. By comparing this algorithm with other algorithms on the synthetic dataset and the real dataset named Yelp, the effectiveness and applicability of the allocation mechanism were verified; Tu et al 14 hoped to assign it to appropriate user according to the characteristics of the task, so as to reduce the cost while increasing the quality of the perceived data. Based on this, a novel task allocation strategy is proposed, which can dynamically allocate tasks to a group of users by capturing the complex interaction between tasks and users; Zhu et al 15 found that when faced with some complex perception tasks, users' completion is generally low.…”
Section: Related Workmentioning
confidence: 99%
“…FL enables distributed computing nodes to collaboratively train models without exposing their sensitive data, thus realizing privacypreserving model training with little loss (or even no loss) of model performance (Wang, Yu, and Han 2020;Yang et al 2019). The crowdsourcing system typically outsources data collection tasks to Internet workers and then aggregates and analyzes the sensing data (Capponi et al 2019;Gummidi, Xie, and Pedersen 2019;Tu et al 2020;Yu et al 2020a). Nevertheless, the centralized platform is generally untrusted and may leak workers' private information.…”
Section: Introductionmentioning
confidence: 99%